2018
DOI: 10.1016/j.ultsonch.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on size, morphology, stability and antioxidant activity of selenium nanoparticles dispersed by a hyperbranched polysaccharide from Lignosus rhinocerotis

Abstract: The differences between ultrasonic and non-ultrasonic approaches in synthesizing Lignosus rhinocerotis polysaccharide-selenium nanoparticles (LRP-SeNPs) were compared in terms of size, morphology, stability and antioxidant activity by UV-VIS, FT-IR, X-ray diffraction (XRD), dynamic light scattering (DLS), transmission electron microscopy (TEM), and energy dispersive X-ray (EDX) with high resolution TEM. Results indicated that the SeNPs were associated with the LRP macromolecules in a physical adsorption patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 52 publications
1
52
1
Order By: Relevance
“…Overall, PSP-SeNPs remained highly dispersible for at least 12 months at 4°C. Their stable time was longer than values reported in the literature for other materials, which showed a stable period of 5 days to 3 months at 4°C 42,44,45 or about 1 month at room temperature. 26,27 Mechanism of formation of PSP-SeNPs Combined with the above results, the formation mechanism of SeNPs and the principal model of PSP capping SeNPs were proposed ( Fig.…”
Section: Dispersion Stability Of Psp-senpscontrasting
confidence: 51%
“…Overall, PSP-SeNPs remained highly dispersible for at least 12 months at 4°C. Their stable time was longer than values reported in the literature for other materials, which showed a stable period of 5 days to 3 months at 4°C 42,44,45 or about 1 month at room temperature. 26,27 Mechanism of formation of PSP-SeNPs Combined with the above results, the formation mechanism of SeNPs and the principal model of PSP capping SeNPs were proposed ( Fig.…”
Section: Dispersion Stability Of Psp-senpscontrasting
confidence: 51%
“…The as-prepared AgNP-DTa with a small size and large specific surface area could therefore provide a lot of active sites to scavenge the free radicals and inhibit the oxidation reactions. 61,62…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 99%
“…Combined with the particle size ( Figure 1b, d and f) and dispersion degree (Table 1- was 0.14 ± 0.05, indicating that the product particles were uniform. Cai et al (2017) reported that SeNPs modified by a hyperbranched polysaccharide from Lignosus rhinocerotis showed a minimum size of 50 nm. Thirty-six percent of the particles had a diameter <50 nm, and a particle size range of 50-100 and 100-300 nm of the particles accounted for 43% and 21%, respectively, which suggested that the (Cai et al, 2017).…”
Section: Preparation Of Sps-senpsmentioning
confidence: 99%
“…Cai et al (2017) reported that SeNPs modified by a hyperbranched polysaccharide from Lignosus rhinocerotis showed a minimum size of 50 nm. Thirty-six percent of the particles had a diameter <50 nm, and a particle size range of 50-100 and 100-300 nm of the particles accounted for 43% and 21%, respectively, which suggested that the (Cai et al, 2017). In comparison with these results, it was clear that the size of SPs-SeNPs synthesized under optimal conditions was much smaller, indicating that the SeNPs were stabilized by SPs.…”
Section: Preparation Of Sps-senpsmentioning
confidence: 99%